Long-term outcome of Bartter syndrome in 54 patients: A multicenter study in Korea - Choi, Naye; Kim, Seong Heon; Bae, Eun Hui; Yang, Eun Mi; Lee, Keum Hwa; Lee, Sang-Ho; Lee, Joo Hoon; Ahn, Yo Han; Cheong, Hae Il; Kang, Hee Gyung; Hyun, Hye Sun; Kim, Ji Hyun (Frontiers in Medicine, 2023)
Introduction: Bartter syndrome (BS) is a rare salt-wasting tubulopathy caused by mutations in genes encoding sodium, potassium, or chloride transporters of the thick ascending limb of the loop of Henle and/or the distal convoluted tubule of the kidney. BS is characterized by polyuria, failure to thrive, hypokalemia, metabolic alkalosis, hyperreninemia, and hyperaldosteronism. Potassium and/or sodium supplements, potassium-sparing diuretics, and nonsteroidal anti-inflammatory drugs can be used to treat BS. While its symptoms and initial management are relatively well known, long-term outcomes and treatments are scarce. Methods: We retrospectively reviewed 54 Korean patients who were clinically or genetically diagnosed with BS from seven centers in Korea. Results: All patients included in this study were clinically or genetically diagnosed with BS at a median age of 5 (range, 0–271) months, and their median follow-up was 8 (range, 0.5–27) years. Genetic diagnosis of BS was confirmed in 39 patients: 4 had SLC12A1 gene mutations, 1 had KCNJ1 gene mutations, 33 had CLCNKB gene mutations, and 1 had BSND mutation. Potassium chloride supplements and potassium-sparing diuretics were administered in 94% and 68% of patients, respectively. The mean dosage of potassium chloride supplements was 5.0 and 2.1 mEq/day/kg for patients younger and older than 18 years, respectively. Nephrocalcinosis was a common finding of BS, and it also improved with age in some patients. At the last follow-up of 8 years after the initial diagnosis, 41% had short stature (height less than 3rd percentile) and impaired kidney function was observed in six patients (chronic kidney disease (CKD) G3, n = 4; CKD G5, n = 2). Conclusion: BS patients require a large amount of potassium supplementation along with potassium-sparing agents throughout their lives, but tend to improve with age. Despite management, a significant portion of this population exhibited growth impairment, while 11% developed CKD G3–G5.